PRAKTIK MANAJEMEN KONFLIK KEPALA MADRASAH: (STUDI DI MTS BUMI SHOLAWAT LAMPUNG TENGAH) - Dewi Masitoh (STAI Asy-Syukriyyah, 2022)
This study aims to describe in a systematic, actual, and accurate manner regrading the conflict management practices of the Madrasah Principal at MTs Bumi Sholawat Central Lampung. The source of the data in this study came from the stakeholders of MTs Bumi Sholawat Central Lampung which are the parties involved in it. Researchers used data collection technique through observation and interviews, then analyzed the data that had been collected from the beginning of the study to the end of the study with data reduction techniques, data presentation, and drawing conclusions. This research was conducted periodically from January 11, 2022 to March 02, 2022. This research was conducted to obtain valid data on conflict management practices for Madrasah Prinsipals at MTs Bumi Sholawat, Central Lampung. The result of this study indicate that the practice of conflict management has been implemented by the Head of Madrasah at MTs Bumi Sholawat Central Lampung. The conflict management practice carried out by the Madrasah Principal of MTs Bumi Sholawat Central Lampung refers to the theory of conflict management styles, namely by practicing the styles of competition, collaboration, compromise, avoidance, and accommodation.